Determinants of Poverty In Java Island 2014-2024 From The Socio-Economic Perspective of Ibn Khaldun - Muh Iqbal Izzudin; Slamet Khilmi (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2026)
Poverty remains a crucial issue in Indonesia. Java Island, which contributes a large portion of the national GDP, still faces uneven development. Ibn Khaldun’s circle of equity model is employed to analyze the determinants of poverty, where the poverty rate represents the role of justice (j), influenced by democracy as a proxy for sharia (S), government expenditure as the role of government (G), economic growth as wealth (W), the open unemployment rate as the role of society or human resources (N), and the Human Development Index as development (g). This study employs a quantitative approach, utilizing the Fixed Effects Model (FEM). The data are obtained from Statistics Indonesia (BPS) and the Directorate General of Fiscal Balance, Ministry of Finance. The results show that the democracy index has no significant effect, government expenditure has a significant negative effect, economic growth has a significant positive effect, unemployment has no significant effect, and the Human Development Index has a significant negative effect on poverty. Simultaneously, the independent variables significantly explain variations in poverty. The integration of Ibn Khaldun’s circle of equity model into this empirical analysis offers a distinct approach to examining poverty issues.